Recurrent extramedullary plasmacytomas without multiple myeloma: A case report with review of the literature. (2022) - Raghuram, Saadvik; Faizal, Bini; Sanjeevan, K.V.; Eapen, Malini; Nair, Indu R.; Philip, Arun; Pavithran, Keechilat
Abstract: Background: Extramedullary plasmacytoma (EMP) is an uncommon presentation and usually occurs in conjunction with multiple myeloma (MM). An EMP without developing MM at any point is an extremely rare presentation, and only seven such cases have been reported in the literature to date. Presentation of Case: : We present a case of EMP, who presented with multiple recurrent lesions in rare sites like nasal cavity, testis and skin without the involvement of bone marrow at any point of disease course. He was treated with multiagent chemotherapy (DT-PACE) and continues to be in remission at 29 months post-chemotherapy, which is the longest amongst all the cases reported so far. Discussion and conclusions: : There are no clearly defined guidelines to treat EMP. Our case had a clinical presentation at very unusual sites and was treated with DT-PACE regimen as against the previous seven reported cases and had the most prolonged period of remission.